2015
DOI: 10.1021/jacs.5b00292
|View full text |Cite
|
Sign up to set email alerts
|

Shape Fixing via Salt Recrystallization: A Morphology-Controlled Approach To Convert Nanostructured Polymer to Carbon Nanomaterial as a Highly Active Catalyst for Oxygen Reduction Reaction

Abstract: Herein, we report a "shape fixing via salt recrystallization" method to efficiently synthesize nitrogen-doped carbon material with a large number of active sites exposed to the three-phase zones, for use as an ORR catalyst. Self-assembled polyaniline with a 3D network structure was fixed and fully sealed inside NaCl via recrystallization of NaCl solution. During pyrolysis, the NaCl crystal functions as a fully sealed nanoreactor, which facilitates nitrogen incorporation and graphitization. The gasification in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
215
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(221 citation statements)
references
References 40 publications
6
215
0
Order By: Relevance
“…To the best of our knowledge, our CNT@Fe-N-PC catalyst showed the best ORR performance in an acidic medium compared with all previously reported Fe-N-C and other non-noble-metal catalysts (Supplementary Table 2). 11,12,13,20,22,27,28,31,[37][38][39][40] In addition to the high activity, we further studied the durability of the CNT@Fe-N-PC catalyst. Figure 3c shows that the current density decay is 12% after 40 000 s of testing, much smaller than that (57%) of commercial Pt/C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, our CNT@Fe-N-PC catalyst showed the best ORR performance in an acidic medium compared with all previously reported Fe-N-C and other non-noble-metal catalysts (Supplementary Table 2). 11,12,13,20,22,27,28,31,[37][38][39][40] In addition to the high activity, we further studied the durability of the CNT@Fe-N-PC catalyst. Figure 3c shows that the current density decay is 12% after 40 000 s of testing, much smaller than that (57%) of commercial Pt/C.…”
Section: Resultsmentioning
confidence: 99%
“…26 Most importantly, the performance of the catalyst obtained is still unsatisfactory, that is, the overpotential versus a commercial Pt/C catalyst is generally more than 60 mV. 20,27,28 In this study, we developed a simple and scalable atomic isolation technique for synthesizing a porous Fe-N-C catalyst with a high concentration of N-coordinated single Fe atoms by pyrrole polymerization on carbon nanotubes (CNTs), followed by Fe 3+ and Zn 2+ (or Li + , Na + and K + ) ion adsorption, and finally one-step pyrolysis. The resulting catalyst is denoted CNT@Fe-N-PC.…”
Section: Introductionmentioning
confidence: 99%
“…16c produced a measured area current activity of 9.9 mA cm −2 at 0.9 V iR-free and a peak power density of 0.9 W cm −2 . Other framework substrate methods, such as a combination of various carbon materials [164][165][166] and synthesis with silica template [131,167,168] or NaCl template [169], were also found to create abundant channels/pores to facilitate mass transportation.…”
Section: Mass Transportationmentioning
confidence: 99%
“…The multi-technique characterization have suggested that the enviable performance should be ascribed to the formation of metal-N complexion structures as well as the carbon nanostructures such as thin graphene sheets and nanofibers [10][11][12]. It has been generally accepted that the formation of uniform and ordered carbon nanostructures is very important in enhancing the catalytic activity [10][11][12][13][14][15][16][17][18][19].…”
Section: Open Accessmentioning
confidence: 99%